Inserção e atuação profissional das engenheiras agrônomas: desafios e estratégias - Carneiro, Ranna Botelho (2022)
This article aims to identify and analyze the main challenges and strategies present in the process of insertion and professional performance of Agronomists in the sergipano productive sector. The research is qualitative with bibliographic survey and application of semi-structured interviews with Agronomist engineers who act as managers, market developers, commercial representatives, enablers and / or consultants in Sergipe. The results show a professional path marked by gender inequality and situations of discrimination that reflected in strategies of conscious and/or unconscious coping in the professional trajectory of these women in the sergipano labor market.